ANALISIS PENGEMBANGAN DESAIN FASHION BERKELANJUTAN DI INDONESIA - Handayani, Rahayu Budhi (Narada : Jurnal Desain dan Seni, 2022)
Analysis of Sustainable Fashion Design Development in Indonesia describes how a design approach strategy can be put into practice to contribute to the development of sustainable fashion. Fashion is an industry that has great potential for Indonesia's creative economy and employment, but on the other hand it has negative social and environmental impacts. Sustainable fashion is a new trend and aesthetic that is developing in urban society. There are various strategies to develop sustainable fashion, one of which is through a design approach. Using a qualitative descriptive approach, this paper further analyzes the implementation of this strategy through purposive sampling of the brand, Sejauh Mata Memandang, as one of the pioneers of sustainable fashion brand in Indonesia. Based on the results of virtual observations and data analysis, it is concluded that there are six sustainable design strategies carried out by Sejauh Mata Memandang that can be used as references as best practices for developing sustainable fashion design in Indonesia.